The pursuit of happiness: Predicting happiness based on anchor theory - Akhtar, Hanif; Firmanto, Ari (Universitas Muhammadiyah Surakarta, 2021)
Happiness has been proven to bring many positive impacts on human life. One theory from the perspective of Islamic Psychology that explains how individuals achieve authentic happiness is the Anchor theory. There are four kinds of individual’s Anchor, that is virtues, self, others and materials. The organization of these anchors determines happiness. This study aims to verify whether Anchor theory is able to predict individual happiness. Subjects in this study were 201 students with an age range of 18-20 years. Happiness is measured by two scales namely Satifaction with Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE), while Anchor structure is measured by Anchor Personality Inventory. Regression analysis is used to invesitigate whether the Anchor structure is able to predict happiness. The results of a single regression analysis showed that Anchor stability was not able to be a predictor of life satisfaction (F = 0.37; P 0.05) and affective balance (F = 2.83; p 0.05). However, the results of multiple regression analysis showed that materials, self, others, and virtues simultaneously act as predictors of life satisfaction (F = 3.06; R2 = 0.059; p 0.05) and affective balance (F = 7.84; R2 = 0.138; p 0.01). Anchor virtues are the most powerful predictors of life satisfaction and affective balance. The implications and suggestions for efforts to increase individual happiness will be discussed in this article.